2011
DOI: 10.1348/135910710x514120
|View full text |Cite
|
Sign up to set email alerts
|

Measuring risk perceptions of skin cancer: Reliability and validity of different operationalizations

Abstract: Conditional likelihood and comparative severity might be better predictors of health behaviour than commonly used operationalizations of risk perception. These measures may be relevant for use in the development and evaluation of intervention programmes, and should be acknowledged by health behaviour theories. Suggestions for future research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
84
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 54 publications
9
84
0
Order By: Relevance
“…Dillard and colleagues (2011), for example, found that the question, ''If I don't get screened, I would feel very vulnerable to getting colon cancer sometime in my life,'' was more strongly associated with colon cancer screening intentions compared with conventional cognitive measures of perceived likelihood. The same results were found for sun protection behaviors in two other studies (Janssen et al, 2010;Janssen et al, 2011). Therefore, cancer risk communication practices may benefit from considering people's feelings of risk.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Dillard and colleagues (2011), for example, found that the question, ''If I don't get screened, I would feel very vulnerable to getting colon cancer sometime in my life,'' was more strongly associated with colon cancer screening intentions compared with conventional cognitive measures of perceived likelihood. The same results were found for sun protection behaviors in two other studies (Janssen et al, 2010;Janssen et al, 2011). Therefore, cancer risk communication practices may benefit from considering people's feelings of risk.…”
supporting
confidence: 79%
“…Recent research on (cancer) risk perceptions showed that affective likelihood beliefs-also called feelings of risk-are more strongly related to health behavior compared with deliberate probability estimates (e.g., Dillard, Ferrer, Ubel, & Fagerlin, 2012;Janssen, van Osch, de Vries, & Lechner, 2010;Janssen, van Osch, Lechner, Candel, & de Vries, 2011;Weinstein et al, 2007). Dillard and colleagues (2011), for example, found that the question, ''If I don't get screened, I would feel very vulnerable to getting colon cancer sometime in my life,'' was more strongly associated with colon cancer screening intentions compared with conventional cognitive measures of perceived likelihood.…”
mentioning
confidence: 99%
“…Using a 5-point response scale (from strongly disagree to strongly agree ), participants completed two items (α = .92) adapted from prior research regarding their conditional perceived skin cancer risk (e.g., “If I don’t protect my skin from the sun, I would feel very vulnerable to getting skin cancer in my lifetime”) (Janssen et al, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…Examples of experiential risk perceptions include gut-level assessments of vulnerability (e.g., “how vulnerable do you feel?” [34] or gist-representations of risk [35]. Experiential risk perceptions are often more predictive of intentions or behavior than are deliberative risk perceptions [34, 36]. …”
Section: Types Of Risk Perceptionsmentioning
confidence: 99%